Análise da complexidade do torque dos extensores do joelho: efeito do envelhecimento, fragilidade e exercício físico - Fiogbé, Elie (Universidade Federal de São Carlos, 2018)
The process of physiological aging involves a series of alterations in the neuromuscular system leading to the reduction of mass and muscle force. Consequently, changes in muscle strength have been investigated in elderly individuals as a tool for detecting geriatric syndromes and declining functional capacity. Consequently, muscle force is routinely assessed in older adults as diagnostic criteria of some geriatric syndromes, and a tool for the investigation of functional capacity declines. However, unlike maximal muscle force, muscle force control indexes allow a better understanding of the neuromuscular system, providing information on the mechanisms governing force production and maintenance, reflecting the sensorimotor control of these individuals. However, several aspects remain uncertain in the study of muscle force control in the elderly. Thus, the effects of aging, muscle contraction intensity, and physical training on large postural muscles force complexity of remain unknown. Investigating these issues will have a great clinical relevance, allowing a better understanding of the age-related changes in the neuromuscular system and its responses to the multicomponent exercise program. In order to elucidate these aspects, this thesis was planned in 3 studies. The Study 1 entitled "Complexity of knee extensor torque: effect of aging and contraction intensity" aimed to investigate the effects of aging and the intensity of isometric contractions on the complexity of knee extensor torque. The results showed that although the knee extensor torque complexity is reduced in the elderly, its relation with the intensity of the contraction is similar to that of the young subjects. Study II entitled "Exercise training in older adults, what effects on muscle force control? A systematic review of randomized clinical trials" aimed to determine the magnitude of the effects of different modalities of physical training on muscle force control variables in older adults, through a systematic review of the literature. The results of this study showed that physical training has a beneficial effect on older adults’ muscle force control. Study III entitled "Effectiveness of a multicomponent training on muscle force control in pre-frail older adults: a blinded randomized controlled trial" aimed to investigate the effectiveness of a multicomponent training program in improving the functional capacity and the complexity of the torque of the patients. knee extensors in pre-frail elderly. The results of this study showed the effectiveness of the multi-component exercise program in improving knee extensor torque complexity and gait speed in pre-frail elderly.
Analysis of complexity of knee extensor torque: effect of aging, frailty and physical exercise
Keywords: Fragilidade; Envelhecimento; Exercício; Controle da força muscular; Entropia; Força muscular; Capacidade funcional; Frailty; Aging; Exercise; Muscle force control; Entropy; Muscle strength; Functional capacity; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL